On-Field Perceptual-Cognitive Training Improves Peripheral Reaction in Soccer: A Controlled Trial - Schumacher, Nils; Reer, Rüdiger; Braumann, Klaus-Michael (Frontiers in Psychology, 2020)
Abilities such as peripheral reaction are of special importance in soccer. Whether these abilities can be improved by sport-specific on-field interventions remains unclear. The aim of the present controlled trial was to investigate the effect of a soccer-specific perceptual-cognitive on-field training on peripheral reaction of highly talented soccer players aged 12 to 13 years. N = 38 male elite athletes from young talent centers were allocated to an intervention (n = 19) and a control group (n = 19). Computer-based peripheral perception tests were conducted pre- and post-intervention. Combining a sport-specific and a juggling task, the intervention was performed once a week (8 weeks, 20 min. per week) in addition to team training. The control group exclusively underwent usual team training. Analyzes show significant differences between the two groups for Peripheral Reaction Time, with significant improvements for the intervention group and none for the control group. Furthermore, results indicate that improvements in peripheral reaction might be due to changes in the reaction time of right-footed players. Future studies should be conducted to clarify the effect of sport-specific on-field training approaches on peripheral reaction time. These analyzes should consider the influence of lateralization on effectivity of perceptual-cognitive on-field training approaches.